PENGGUNAAN ASAM LAKTAT SEBAGAI ACIDIFIER DALAM PAKAN YANG MENGANDUNG PROBIOTIK TERHADAP INDEKS TELUR DAN MASSA TELUR AYAM SENTUL - Rizki Ikhbar Wika Pratama; Bambang Hartoyo; Elly Tugiyanti (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The research objective was to assess The Addition of an Acidifier in Feed Containing Probiotics of Egg Index and Egg Mass of Sentul Chickens. Materials and Methods. The material used was 60 female sentul chickens aged 5 months, with 4 treatments, 5 repetitions, and each experimental unit consists of 3 chicken. Treatment: R0 = basal feed; R1 = basal feed + probiotic with lactic acid acidifier 0.5%; R2 = basal feed + probiotic with lactic acid acidifier 1.0%; R3 = basal feed + probiotic with lactic acid acidifier 1.5%. Design with CRD (completely randomized design) and data analysis using ANOVA. Results. The results of the analysis of variance showed that the treatment had no significant effect (P> 0.05) on egg index and egg mass of Sentul chicken. Conclusion. It was concluded that the addition of lactic acid as an acidifier in feed containing probiotics up to a level 1,5% was not able to improve the quality of egg index and egg mass of Sentul chickens.